Neonatal Resuscitation in Primary Health Care Facilities - Gusti Ayu Putu Ika Bella Saptaning Astyari; Rabel Relianta Zagoto; Oby Mesakh Ngahu (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2022)
Background : Neonatal resuscitation is an action that must be done in the first minute when a newborn with severe asphyxia is born.Case Illustration : The case was infant whom born spontaneously from 41 years old woman, G7P6A0 in primary health care facilities at Kokoda Utara District, with a condition did not cry or breathe, the skin color was bluish, there was no muscle tone, APGAR score was 0. Infant did not show any response, so we gave positive pressure ventilation using a bagging mask and chest compression with compression techniques by using both thumbs and other fingers around the chest supporting from the back, with a ratio of 3 compressions per 1 breath. After 60 minutes of resuscitation, the baby can cry loudly and the APGAR score is 10, heart rate was 140 beats per minute, breathing is 35 times per minute, SpO2 98%, blood glucose is 46 mg/Dl, body weight 2300 grams, body length 40 cm, head circumference 33 cm, chest circumference 32 cm, which indicates that the baby is no longer in asphyxia.Conclusion : Rapid initial assessment of the newborn and appropriate implementation of neonatal resuscitation determines success and reduces mortality.